2019
DOI: 10.1016/j.celrep.2018.12.088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Genetically Encoded Voltage Indicators

Abstract: Highlights d Side-by-side comparison of genetically encoded voltage indicators (GEVIs) d Side-by-side evaluation of 8 GEVIs in cultured neurons with 1-photon imaging d Side-by-side evaluation of 4 GEVIs in vivo with 1-photon and 2-photon imaging d Detection of optical field potential (OFP) with GEVIs in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 63 publications
5
139
1
Order By: Relevance
“…Importantly, it is not clear whether the increased fluorescence intensity is a result of greater 1:1 entrainment, or due to other activation properties such as bursting. Newer developments in genetically encoded voltage (GEVI) and calcium indicators (GECI) with faster kinetics may be able to more comprehensively address these questions [93][94][95]. However, it should be noted that current GEVIs do not provide comparable spatial resolution and suffer from lower signal to noise ratio [96].…”
Section: Limitationsmentioning
confidence: 99%
“…Importantly, it is not clear whether the increased fluorescence intensity is a result of greater 1:1 entrainment, or due to other activation properties such as bursting. Newer developments in genetically encoded voltage (GEVI) and calcium indicators (GECI) with faster kinetics may be able to more comprehensively address these questions [93][94][95]. However, it should be noted that current GEVIs do not provide comparable spatial resolution and suffer from lower signal to noise ratio [96].…”
Section: Limitationsmentioning
confidence: 99%
“…For example, recent studies have demonstrated that opsin-based GEVIs (i.e. Ace2N-2AA-mNeon, MacQ-mCitrine) do not work under multiphoton illumination, the technique of choice for deep tissue imaging necessary in highly scattering media such as the mammalian brain 8,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…1(b)], leading to a halving of the maximum frame rate. This limitation becomes important when investigating fast events such as calcium transients 12,13 or very large volumes, 4,9,[14][15][16] but can be overcome by generating two independent parallel light-sheets within the field of view (FOV) and by synchronizing them with the two rolling shutters, at the cost of increased complexity. A first such system has been realized using a DLSM 17 where two focused illuminating beams, coming from two identical but facing each other objectives, scan half the FOV each in opposite directions.…”
Section: Introductionmentioning
confidence: 99%